CRISPR-Cas13d Induces Efficient mRNA Knockdown in Animal Embryos - Kushawah, Gopal (2020)
Early embryonic development is driven exclusively by maternal gene products deposited into the oocyte. Although critical in establishing early developmental programs, maternal gene functions have remained elusive due to a paucity of techniques for their systematic disruption and assessment. CRISPR-Cas13 systems have recently been employed to degrade RNA in yeast, plants, and mammalian cell lines. However, no systematic study of the potential of Cas13 has been carried out in an animal system. Here, we show that CRISPR-RfxCas13d (CasRx) is an effective and precise system to deplete specific mRNA transcripts in zebrafish embryos. We demonstrate that zygotically expressed and maternally provided transcripts are efficiently targeted, resulting in a 76% average decrease in transcript levels and recapitulation of well-known embryonic phenotypes. Moreover, we show that this system can be used in medaka, killifish, and mouse embryos. Altogether, our results demonstrate that CRISPR-RfxCas13d is an efficient knockdown platform to interrogate gene function in animal embryos.